Conceptual Design of Shielded Metal Arc Welding Workstation: Work Posture and Bead Dimension Consideration - Halim, I.; Radin Umar, R. Z.; Ahmad, N.; Abdul Rahim, R.; Zakaria, N. F. I. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
The aim of this study was to propose a conceptual design of SMAW workstation which considered work postures of welders and weld bead dimensions. This study applied full factorial design of experiment. The independent variables were table height, table surface inclination, and work position. Meanwhile the dependent variables were bead height, bead width, and RULA score. Results of analysis of variance showed that the table height, table surface inclination, and work position have an effect on bead width and bead height. This study concluded that the proposed SMAW workstation can offer acceptable bead dimensions when it is designed with adjustable table height, table surface is flat (0°), and work position is standing. However, the work posture still requires further investigation.